2017
DOI: 10.3892/mco.2017.1356
|View full text |Cite
|
Sign up to set email alerts
|

The optimum marker for the detection of lymphatic vessels

Abstract: Podoplanin, lymphatic vessel endothelial hyaluronic acid receptor-1, prospero-related homeobox-1 and vascular endothelial growth factor receptor 3 have been demonstrated to have crucial roles in the development of the lymphatic system and lymphangiogenesis process by combining with their corresponding receptors. Thus, the four markers have been widely used in labelling lymphatic vessels for the detection of lymphangiogenesis and lymphatic vessel invasion. Numerous authors have aimed to identify the roles of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 69 publications
1
46
0
Order By: Relevance
“…CD31 is a traditional marker of blood vessels that is weakly expressed on lymphatics [110]. However, podoplanin is a more specific marker of lymphatic endothelium since it is absent from blood vessel endothelium [111]. Conversely, LYVE-1 has been found to be expressed in some macrophages and blood vessels, including liver sinusoids [110].…”
Section: After Transplantationmentioning
confidence: 99%
“…CD31 is a traditional marker of blood vessels that is weakly expressed on lymphatics [110]. However, podoplanin is a more specific marker of lymphatic endothelium since it is absent from blood vessel endothelium [111]. Conversely, LYVE-1 has been found to be expressed in some macrophages and blood vessels, including liver sinusoids [110].…”
Section: After Transplantationmentioning
confidence: 99%
“…(1:200, catalog number 14044380, Thermo Fisher Scientific) and podoplanin (1:300, catalog number 127408, BioLegend, San Diego, CA) to label the lymphatic vasculature (14). To visualize the immune cell response after injury in tendon, tissues were fixed in ice cold acetone for ten minutes, blocked with 5% goat serum for one hour, and stained with biotinylated antibodies against CD11b to identify myeloid cells ( Invitrogen) were used to detect primary antibodies that were not already conjugated to a fluorophore.…”
Section: Surgeriesmentioning
confidence: 99%
“…4 b). After purification, > 95% of the cells expressed the arteriovenous EC marker CXCR4 [ 33 , 34 ] and the arterial marker DLL4 [ 33 , 35 – 37 ], while ~ 16% expressed the venous marker EphB4 [ 38 , 39 ], but expression of the lymphatic EC marker podoplanin [ 40 , 41 ] was undetectable (Fig. 4 c).…”
Section: Resultsmentioning
confidence: 99%
“…Three cell lines were reprogrammed from the cells of patients with diseases or disease symptoms that are associated with endothelial dysfunction: T2DM (two lines) [ 23 ] and Hutchinson-Gilford progeria syndrome (one line) [ 24 , 25 ]. Analysis of the expression of markers for arterial (DLL4 and CXCR4) [ 33 – 37 ], venous (EphB4 and CXCR4) [ 33 , 34 , 38 , 39 ], and lymphatic (podoplanin) [ 40 , 41 ] ECs indicated that the population of differentiated cells contained only arteriovenous ECs. hiPSC-ECs formed tubular structures and EC lumens in vitro and restore perfusion and improve vascularity in a murine HLI model after transplantation in vivo.…”
Section: Discussionmentioning
confidence: 99%